BENTUK PENGASUHAN ORANG TUA DALAM MENUMBUHKAN KEMAMPUAN SOSIAL ANAK DI DESA NARU - Benedikta Eno Wio; Konstantinus Dua Dhiu; Karmelia Rosfinda Meo Maku; Efrida Ita (Jurnal Santiaji Pendidikan (JSP), 2026)
Research entitled "Parental Care Forms in Cultivating Children's Social Skills in Naru Village". This study aims to determine and describe various forms of parenting applied by parents to early childhood and analyze the role of parental care in cultivating children's social skills in Naru Village. The urgency of this study is to determine the social development of early childhood as the basis for children's ability to adapt, communicate, and establish positive relationships with their surroundings. In Naru Village, there are still parents who do not understand the application of appropriate parenting patterns in cultivating children's social skills, coupled with busyness, limited time with children, and the influence of the social environment that becomes an obstacle in the parenting process. The type of research used is qualitative descriptive research. In this case the approach used is a case study. Data collection techniques used in this study are observation, interview, and documentation techniques. Activities in analyzing data consist of data reduction, data presentation and drawing conclusions. The research subjects include parents who have children aged 4-6 years as the main focus, PAUD teachers who provide supporting information about children's social behavior at school, and children aged 4-6 years as objects of observation. The results of the study revealed that parents in Naru Village apply various forms of parenting, namely authoritative (democratic), authoritarian, permissive, and less involved (neglectful) parenting. Among these four patterns, authoritative parenting is the most widely applied and has been proven to have a positive influence on the development of children's social skills, including the ability to communicate, cooperate, share, and foster empathy. These findings provide important implications for parents and educators in selecting and implementing appropriate parenting patterns to support the development of social skills in early childhood, especially in rural communities.